Complex channel characterization - Tay, Ron Yingren. (2009)
This report document the preparatory work of the joint collaboration project between NTU and DSO National Laboratories of the flight trial performed on the 12th February 2009. The objective of the project was to characterize the air to land channel of the wireless link using a frequency of 5.69GHz in the C Band.